Underwriting Results, Investment Results and Risk Based Capital on Profit of General Insurance Companies in Indonesia - Markonah Markonah; Irma Selliamanik (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
An insurance business is a business that provides services in risk re-insurance. This study aims to analyze Premium Income, Underwriting Results, Investment Returns and Risk Based Capital on Profits of General Insurance Companies in Indonesia. The method used in this study is documentation techniques through OJK reports and financial reports for 8 insurance companies in Indonesia from 2016 to 2020 so that the population is 40 data. The sampling technique is saturated sampling, where the entire population is taken as a sample, so that the total sample is 40 data. The results of the study show that investment returns and risk based capital have a positive and significant effect on earnings, while premium income and underwriting results have no significant effect on profits.